Delayed administration of the GLP-1 receptor agonist liraglutide improves metabolic and functional recovery after cerebral ischemia in rats. (22nd February 2017) - Dong, Wenbin; Miao, Yunping; Chen, Aiying; Cheng, Min; Ye, Xiaodi; Song, Fahuan; Zheng, Gaoli
Highlights: We demonstrated metabolic and functional recovery after delayed treatment with the GLP-1R agonist liraglutide after cerebral ischemia in rats. Liraglutide improves metabolic and functional recovery after cerebral ischemia in a dose-dependent manner. Liraglutide improves metabolic and functional recovery by promoting neurovascular remodeling through its receptor, GLP-1R. Abstract: Glucagon-like peptide 1 receptor (GLP-1R) agonists administered before or immediately after induction of experimental stroke have been shown to provide acute neuroprotection. Here, we determined whether delayed treatment with a GLP-1R agonist could improve metabolic and functional recovery after stroke. Rats were subjected to middle cerebral artery occlusion (MCAO) and given the well-established GLP-1R agonist liraglutide (50, 100, or 200 μg/kg) or normal saline (NS) daily for 4 weeks, starting 1 day after MCAO. Cerebral glucose metabolism and neurological deficits were evaluated using 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) imaging and modified neurological severity score (mNSS) test. Levels of neuronal nuclei (NeuN), glial fibrillary acidic protein (GFAP), von Willebrand factor (vWF), and GLP-1R were assessed by immunohistochemical staining and Western blot analysis. PET imaging showed that animals treated with liraglutide had significantly higher 18 F-FDG accumulation in the cerebral infarction compared with animals treated with NS. Liraglutide significantly reduced the mNSS score. It also greatly increased the expression of NeuN, GFAP, vWF, and GLP-1R in the cerebral ischemic area at postoperative week 4. These results demonstrated metabolic and functional recovery after delayed treatment with liraglutide in a rat model of cerebral ischemia.